Pharmacists’ interventions in minimising medication misadventure in children with cancer - Ramadaniati, Hesty Utami (Curtin University, 2015)
This study evaluated 1741 interventions by clinical pharmacists to reduce medication misadventure in three clinical units of a children’s hospital in Perth, Australia, documented using snapshot self-report and observation. Commonly, pharmacists’ interventions involved taking medication histories, patient counselling and/or drug therapy changes. Active interventions were randomly assessed by an expert panel for their clinical significance. Root cause analysis was used to assess healthcare professionals’ ability to evaluate medication errors causes and formulate preventative strategies.